Praktik Literasi Dalam Mewujudkan Pendidikan Yang Memerdekakan Dalam Memanusiakan Dan Berpihak Terhadap Peserta Didik - Salwa Sausan; Liesna Andriany (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research uses a qualitative approach and literature study to describe the role of literacy practices in learning that liberates students. The data was analyzed descriptively, showing that appropriate literacy practices can create liberating learning for students.The aim of this study is to find out new innovations from the Minister of Education and Culture, namely the Teacher Mobilization Program. This program is expected to produce transformation agents in the education ecosystem to produce students with global competence and Pancasila character. Descriptive qualitative methods were used in this study report with data sources from the oral narrative of the Indonesian Ministry of Education and Culture YouTube Channel. The results of the study explain that the Teacher Mobilization Program aims to create education that is liberating, humanizing and pro-student.